ANALYSIS AND PRIORITIES FOR IMPROVING SERVICE QUALITY AT DANI BAKERY USING THE SERVQUAL METHOD, IPA, PGCV INDEX - Arthur Hetharia (LPPM Politeknik Saint Paul Sorong, 2023)
Based on the results of initial interviews with Dani Bakery, it is known that the decline in turnover over the last 5 years of around 50% was due to the Covid-19 pandemic and also the increasing number of competitors in Sorong Regency and Sorong City, totaling 11 bakery businesses so that consumers have many alternatives to choose from buy quality bread. Therefore, measuring the level of service quality is very necessary to determine the gap between the perceptions and expectations of Dani Bakery customers in order to improve the quality of service of Dani Bakery Bread. The method used is the Servqual method to determine the level of service quality, Importance-Performance Analysis and Potential Gain in Customer Value are used to determine service improvement priorities. The number of respondents in this study was 93 respondents and to collect data the researchers used convenience sampling or accidental sampling techniques. Based on the calculation results of the service quality dimension attributes, the average Servqual score is negative (-0.499), which means that the service quality at Dani Bakery is perceived as poor, while the main priority of service improvement at IPA is in quadrant A based on the PGCV index value, namely in the attributes P11-E11 (long-lasting products) with a PGCV value of 7.430, attributes P12-E12 (delicious taste) with a PGCV value of 6.743 and attributes P2-E2 (flavor variants already represent customer desires) with a PGCV value of 5.419.